NEW INTERVENTIONS IN FUMIGATING WITH APARAJITHA DHOOMA CHOORNAM - Priya Prasannakumar; Divya S Balachandran (AYUSHDHARA, 2021)
Aparajitha dhooma choornam is a traditional Ayurvedic medicine used to disinfect the environment. The microbicidal properties of Ayurvedic Dhoopana have been previously documented. The safety and efficacy of herbal products can be improved by incorporating modern technology while fumigating. The present study aims to show the efficacy of fumigation with Aparajitha dhooma choornam sticks in reducing microbial flora of work spaces so that it can be used conveniently on a regular basis to improve air quality and reduce the incidence of spread of airborne diseases. Bioassay studies were also carried out to check the insecticidal activity of Dhoopana against both larvae and adult mosquitoes found at site. Thus fumigation with Aparajitha dhooma choornam sticks and powder form was found to be effective in not only reducing microbial load but also in possessing insecticidal activity.